Reinterpretasi Masa Iddah Perempuan Karir: Studi Pemikiran KH. Husein Muhammad Dalam Perspektif Maqasid Syariah - Mukti Thabrani, Abdul; Mega Wati, Firda (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the reinterpretation of the iddah period of career women in the perspective of KH's thought. Husein Muhammad by using the maqasid sharia approach. Normatively, iddah is a waiting period for women after divorce or the death of their husbands to maintain honor, ensure pregnancy status, and provide space for emotional recovery. However, the classical fiqh understanding that emphasizes al-habs fi al-bait (staying at home) is often patriarchal and irrelevant to the conditions of modern women who are actively working. This study uses a literature study method with a socio-historical approach, and a descriptive-analytical content analysis of KH's work. Husein Muhammad, classical fiqh literature, as well as secondary sources related to sharia maqasid and gender. The results of the study show that KH. Husein reinterpreted the law of iddah to be in accordance with the goals of the sharia which are oriented towards justice, benefit, and protection of human dignity. She rejects textual views that limit women's space of movement, because it is contrary to the values of hifz al-nafs, hifz al-mal, and hifz al-din. KH's thoughts. Husein Muhammad reflects a form of ijtihad maqasidi that bridges tradition and modernity, presenting an Islam that is humanist, contextual, and gender-correct